PENGUJIAN VICKERS HARDNESS HASIL ELECTROPLATING NIKEL PADA PERMUKAAN ALUMINIUM PADUAN 5052 - CHANDRA GUMELAR, (2020)
Aluminum 5052 is a type of aluminum alloy 5000 series. Its use, has a wide range in the manufacture of components that include the field of shipping, aircraft industry, building structure framework etc. the superior feature of aluminum alloy 5052 is its high corrosion resistance. However, mechanical properties such as low defense are only 73 VHN with a load of 30kg-f and a concentration time of 10 seconds. an alternative to increase its hardness is through the electroplating process, where 12 pieces of workpiece aluminum alloy 5052 are the same size, solutions with nickel which increase higher in each variation of voltage and time of different electrolysis. the results of the electroplating process show the thickness of the nickel layer which varies with variations in voltage variations and time variations of the nickel electroplating process on the surface of aluminum alloy 5052. The lowest thickness of the nickel layer is 11.75 μm with a 17.8% increase process, corresponding to a total amount of 194.6 μm with a 91.7% process efficiency. VHN value (Vickers Hardness number) VHN value of the lowest nickel electroplating result was 81.55 VHN by comparing only 12% and for high thickness nickel coating 144.25 VHN with an added value of hardness of an average of 100%.